2022
DOI: 10.1177/15248380221129595
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Bullying Victimization and Perpetration Among the School-Aged Population in Chinese Communities: A Systematic Review and Meta-Analysis

Abstract: Though bullying was predominantly documented in Western societies, increasing attention has been paid to bullying in Chinese communities during recent years. It remains unknown whether bullying among youngsters in the Chinese communities is similar to or different from their counterparts in Western societies. A systematic review was primarily conducted in English and Chinese databases from the start to December 31, 2021. This study estimated the prevalence of overall (integrating both face-to-face and cyber fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…CV = cyberbullying victimization; TV = traditional bullying victimization. CI [16.7,25.6]) of youth were victims of traditional bullying, and 9.6% (95% CI [6.5, 13.9]) of youth experienced cyberbullying victimization (Xing et al, 2022). Numerous studies consistently shown that youth's experiences of cyberbullying and traditional bullying victimization significantly predicted a wide range of psychosocial problems and academic maladjustment (Halliday et al, 2021;Moore et al, 2017).…”
Section: Cyberbullying and Traditional Bullying Victimization And Sui...mentioning
confidence: 99%
See 1 more Smart Citation
“…CV = cyberbullying victimization; TV = traditional bullying victimization. CI [16.7,25.6]) of youth were victims of traditional bullying, and 9.6% (95% CI [6.5, 13.9]) of youth experienced cyberbullying victimization (Xing et al, 2022). Numerous studies consistently shown that youth's experiences of cyberbullying and traditional bullying victimization significantly predicted a wide range of psychosocial problems and academic maladjustment (Halliday et al, 2021;Moore et al, 2017).…”
Section: Cyberbullying and Traditional Bullying Victimization And Sui...mentioning
confidence: 99%
“…Both cyberbullying and traditional bullying are widespread phenomena around the world, with nearly one-third of children and adolescents experiencing bullying victimization (Koyanagi et al, 2019). A recent meta-analysis among Chinese adolescents found that approximately 20.8% (95% CI [16.7, 25.6]) of youth were victims of traditional bullying, and 9.6% (95% CI [6.5, 13.9]) of youth experienced cyberbullying victimization (Xing et al, 2022). Numerous studies consistently shown that youth’s experiences of cyberbullying and traditional bullying victimization significantly predicted a wide range of psychosocial problems and academic maladjustment (Halliday et al, 2021; Moore et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Adolescents repeatedly indulge in bullying behavior ( 2 ). One study reported a high prevalence of bullying in Chinese adolescents ( 3 ). The estimated prevalence of face-to-face bullying victimization and perpetration was 20.8 and 10.3%, respectively, while the estimated prevalence of cyberbullying victimization and perpetration was 9.6 and 8.4%, respectively, in the Chinese school-age population ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study reported a high prevalence of bullying in Chinese adolescents ( 3 ). The estimated prevalence of face-to-face bullying victimization and perpetration was 20.8 and 10.3%, respectively, while the estimated prevalence of cyberbullying victimization and perpetration was 9.6 and 8.4%, respectively, in the Chinese school-age population ( 3 ). Bullying victimization not only leads to depression, anxiety, and suicide in children but also impacts their educational and economic outcomes ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%